Absorption of energy exploitation during impact of aircraft - Antanas Žiliukas; Nina Fiodorova (Aviation, 2004)
The article shows the variation of stopping distance as a function of deceleration and velocity change derived from the standard Newtonian equations for assumed constant acceleration. Note that the time to stop is equal for all three triangular deceleration‐time pulses but that the stopping distances are not. Minimum stopping distance is achieved with a rectangular pulse, and hence it is the most desired pulse shape from a consideration of deceleration from maximum velocity at a given deceleration level in the shortest possible distance.